Development and Characterization of Gold Nanoparticle-Modified SPCEs for the Electrochemical Sensing - Yuris Diksy; Ardina Purnama Tirta; Herawati; Reza Mulyawan; Moh Hayat; Udin Asrorudin (Indonesian Scholar Society, 2025)
Gold nanoparticles were successfully synthesized by reducing HAuCl4 using jengkol (Archidendron pauciflorum) extract as a reductant. The synthesized gold nanoparticles were characterized by UV–vis spectroscopy and particle size analyzer (PSA). The synthesized gold nanoparticles were deposited on the screen printed carbon electrode (SPCE) substrate using 2 methods, drop casting and differential pulse voltammetry over a potential range of (-1500) mV to 600 mV, scan rate of 100 mV/s for 5 cycles. The surface plasmon resonance (SPR) band of UV– Vis spectrum at 530.7 nm confirmed the presence of gold nanoparticles. The results of Au nanoparticle characterization using PSA show that the size of the Au-NPs formed is 33.5 nm with an optimal HAuCl4 concentration of 0.20 mM. Characterization of gold nano-deposited SPCE was carried out by measuring the peak current of the 1 mM K3Fe(CN)6/K4Fe(CN)6 system in KCl electrolyte solution (0.1 M) using cyclic voltammetry over a potential range of (-500) mV to 1000 mV, scan rate 100 mV/s for 5 cycles. Gold nanoparticles deposited by differential pulse voltammetry showed a higher current response compared to drop casting deposition.